MODEL GROUP INVESTIGATION (GI) DIPADU PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BEKERJA ILMIAH DAN KEMAMPUAN KOGNITIF SISWA KELAS X-A1 SMAN 2 MALANG - Erfitra Rezqi Prasmala (UNIVERSITAS PGRI MADIUN, 2016)
The purpose of this study to improve (1) the skills of scientific work, (2) the cognitive abilities of students of class X-A1 at SMAN 2 Malang through the application of models Group Investigation (GI) combined with the Problem Based Learning (PBL). Type of research is Action Research Action (PTK) with research subjects-A1 class X SMAN 2 Malang. Data collected by the research instrument consisting of a sheet of observation skills of scientific work, scientific work reports, students' cognitive abilities tests, field notes and enforceability of teacher learning, and qualitatively analyzed descriptively. Results of the study are: (1) Model Group Investigation (GI) combined Problem Based Learning (PBL) improve the skills of scientific work class X-A1 at SMAN 2 Malang, (2) Model Group Investigation (GI) combined Problem Based Learning (PBL) improve the cognitive abilities of X-A1 grade students at SMAN 2 Malang. Based on the discussion of the proposed suggestions in this study were: (1) application of the combined GImodel of PBL, can not be carried out independently entirely by students, (2) the need for time management as effectively as possible, to avoid the addition of excess time.